Chemical composition and lipoxygenase activity in soybeans (Glycine max L. Merr.) submitted to gamma irradiation - Barros, Erica Amanda de [UNESP]; Broetto, Fernando [UNESP]; Bressan, Dayanne F. [UNESP]; Sartori, Maria M. P. [UNESP]; Costa, Vladimir E. [UNESP] (Elsevier B.V., 2014)
Soybeans are an important food due to their functional and nutritional characteristics. However, consumption by western populations is limited by the astringent taste of soybeans and their derivatives which results from the action of lipoxygenase, an enzyme activated during product processing. The aim of this study was to evaluate the effect of gamma irradiation on the chemical composition and specific activity of lipoxygenase in different soybean cultivars. Soybeans were stored in plastic bags and irradiated with doses of 2.5, 5 and 10 kGy. The chemical composition (moisture, protein, lipids, ashes, crude fiber, and carbohydrates) and lipoxygenase specific activity were determined for each sample. Gamma irradiation induced a small increase of protein and lipid content in some soybean cultivars, which did not exceed the highest content of 5% and 26%, respectively, when compared to control. Lipoxygenase specific activity decreased in the three cultivars with increasing gamma irradiation dose. In conclusion, the gamma irradiation doses used are suitable to inactivate part of lipoxygenase while not causing expressive changes in the chemical composition of the cultivars studied. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cultivars; Ionizing radiation; Enzyme; Specific activity; Oxidation